Effectiveness of GnRH Antagonists and Agonists in Patients with Hormone-Sensitive Prostate Cancer: A Retrospective Study - Zhenghao Liu; Chunguang Yang; Xing Zeng; Chunjin Ke; Jihua Tian; Zhihua Wang; Zhiquan Hu (Applied Bionics and Biomechanics)
Objective. To assess the effectiveness of gonadotropin-releasing hormone (GnRH) antagonists and agonists in the treatment of patients with hormone-sensitive prostate cancer (HSPC), thus providing valid data support for their clinical treatment. Methods. We collected 52 and 65 HSPC patients treated with GnRH antagonists and agonists, respectively, in Tongji Hospital, Tongji Medical College of HUST between May 2019 and April 2021. Prostate-specific antigen (PSA) levels before and after treatment were recorded and analyzed. Further, univariate and multivariate logistic regressions were used to analyze the influencing factors of PSA control rate in HSPC patients. Results. In patients receiving antagonist, the control rate of prostate-specific antigen (PSA) was 54.28% and 88% without and with abiraterone, respectively, and 47.91% and 72% in patients treated using agonist without and with abiraterone. In 32 pairs of patients obtained via propensity score matching, the PSA control rates were 84.38% and 53.13% for those receiving antagonists and agonists, respectively, and 66.67% and 50% for those without abiraterone, respectively. In addition, univariate logistic regression analysis showed that the type of androgen deprivation therapy (ADT) drugs and combined use of abiraterone had a significant effect on the control rate of PSA. Further multivariate logistic regression revealed that GnRH antagonists in ADT drugs were risk factors for PSA control rate. Conclusion. The PSA control rate of HSPC patients treated with GnRH antagonist is significantly higher than that of the agonist group, and the use of GnRH antagonist is an independent predictor of PSA control rate.